American Protectionist Thought: The Economic Philosophy and Theory of the 19th Century American Protectionists - Mathew A. Frith (Federation University Australia, 2024)
This study contributes to economic knowledge by recovering the system of economic philosophy and theory developed by the 19th century American Protectionists. The account provided in this thesis is comprehensive and covers all major aspects of their theoretical system. Put simply, this study provides an explication and clarification of the economic philosophy and theory of this important, yet neglected, school of economic thought. In doing so, the approach undertaken is one which goes beyond the writings of Alexander Hamilton, Friedrich List, and Henry Charles Carey, and instead draws upon the full corpus of American Protectionist literature. By drawing upon the writings of roughly seventy economists and statesmen from within this neglected tradition, this study has been able to consolidate and distil their ideas into a general and coherent system of economic theory. This thesis therefore recovers an important and original lens through which to interpret and understand the workings of the economy. This is important for both economists and historians of economic thought alike. Whereas most literature in the history of economic thought relegate the American Protectionists to a position of insignificance, this study demonstrates that their system is a refined and sophisticated doctrine of economic thought which rivalled, and even surpassed, other 19th century schools of economic thought. Indeed, against the Whig theory of history, which presupposes that economic knowledge progresses in a linear and upward manner, this thesis contends that superior theories can often be displaced by inferior ones, with knowledge being lost as a consequence. This thesis therefore advances the view that the system of thought developed by the American Protectionists is an example of where important and relevant economic knowledge has been lost. Rediscovering this lost knowledge is thus important not only for purely historical reasons, but for its ability to aid modern economic analysis.
hdl:1959.17/200770
Keywords: 330; History of economic thought; Protectionism; American School; American System; Alexander Hamilton; Henry Charles Carey; Friedrich List; John Rae; Economic development; International trade; American economic thought; Dynamic economic growth